Host specificity of coral-associated fauna and its relevance for coral reef biodiversity - van der Schoot, Roeland J.; Hoeksema, Bert W. (International journal for parasitology, 2024)
[Display omitted] •Corals support coral reef biodiversity by acting as hosts for symbionts.•Four major taxa of coral parasites were compared for their host specificity.•Totals of 203 coral-associated invertebrates and 335 host coral species were recorded.•Coral barnacles and gall crabs are more host-specific than serpulids and date mussels.•Coral symbionts in the Indo-Pacific are more host-specific than those in the Atlantic region. Coral-associated fauna predominantly consists of invertebrates and constitutes an important component of coral reef biodiversity. The symbionts depend on their hosts for food, shelter and substrate. They may act as parasites by feeding on their hosts, by overgowing their polyps, or by excavating their skeletons. Because some of these species partly reside inside their hosts, they may be cryptic and can easily be overlooked in biodiversity surveys. Since no quantitative overview is available about these inter-specific relationships, this present study adresses variation in host ranges and specificity across four large coral-associated taxa and between the Atlantic and Indo-Pacific oceans. These taxa are: coral barnacles (Pyrgomatidae, n=95), coral gall crabs (Cryptochiridae, n=54), tubeworms (Serpulidae, n=31), and date mussels (Lithophaginae, n=23). A total of 335 host coral species was recorded. An index of host specificity (STD) was calculated per symbiont species, based on distinctness in taxonomic host range levels (species, genus, family, etc.). Mean indices were statistically compared among the four associated taxa and the two oceanic coral reef regions. Barnacles were the most host-specific, tubeworms the least. Indo-Pacific associates were approximately 10 times richer in species and two times more host-specific than their Atlantic counterparts. Coral families varied in the number of associates, with some hosting none. This variation could be linked to host traits (coral growth form, maximum host size) and is most probably also a result of the evolutionary history of the interspecific relationships.